Perbedaan pengetahuan menyikat gigi melalui penyuluhan dengan metode ceramah dan pemutaran video kartun pada murid sekolah dasar - Arnetty, Arnetty; Ifitri, Ika; Warman, Anses; Anggraini, Elsa Putri Ayu; Amiruddin, Amiruddin (Poltekkes Kemenkes Aceh, 2024)
Background: The reason why someone neglects dental and oral hygiene is a lack of knowledge. Knowledge is closely related to education. Dental and oral health education is a method to motivate individuals to clean their teeth and mouth effectively.Objectives: The aim of the research was to determine differences in toothbrushing knowledge through counseling using lecture methods and cartoon videos to students in grades IV and V at SDN 04 Air Pura, Pesisir Selatan Regency.Methods: The type of research used is a quasi-experimental type with a